Psychological Impact of Victim of Psychical Violence in Household - Samosir, Nettina; Sirait, Kilian (PT. Riset Press International, 2025)
Domestic violence (KDRT) is very complex violence and requires comprehensive treatment, and most of the victims are women (wives). The impact of violence against a wife is experiencing physical pain, mental stress, decreased self-confidence and self-esteem, experiencing a feeling of helplessness, experiencing dependence on a husband who has abused her, experiencing post-traumatic stress, experiencing depression, and wanting to commit suicide. The rate of domestic violence tends to increase every year, indicating that victims are starting to realize that acts of domestic violence are not something that can be normalized, so victims have the right to fight for their right to live safely and better. Marriage, which should be a comfortable space for a couple, has become the scariest space for some women. The factors that cause violence against women in the household, especially by husbands against wives, are very diverse. Domestic violence is a behavior that has a very complex impact on women who are victims of domestic violence. These acts of violence produce psychological impacts on women who are victims of domestic violence. One of the handling efforts is to fulfill the rights of women who are victims of domestic violence. Understanding the culture of equality is very much needed in the lives of couples, families, and society.